Pengaruh Program Sapa Mantan terhadap Minat Mendengar Radio Prambors (Survey Pendengar Remaja di Jakarta) - Widodo, Athaya Rana; Agustrijanto, Agustrijanto (UNIVERSITAS KALBIS, 2024)
The SAPA MANTAN program highlights the conflict and drama of the love story experienced by the character concerned. Various kinds of responses were expressed by young people on social media regarding the SAPA MANTAN broadcast, some of the young people liked the show with this theme, but some did not like it. This study aims to determine the effect of the DGITM Radio Prambors Program on Adolescent Listening Interests in Jakarta. This study uses a positivistic paradigm with a quantitative approach by using questionnaires as a survey method. This study uses stimulus response theory by testing the Pearson's Correlation Product Moment correlation with a sig value of 0.811, which means that there is a positive relationship between variables X and Y, in linear calculations it is stated that variable X has an effect on variable Y with <0.05. In the calculation of the coefficient of determination, the proportion of variable X in influencing Variable Y is 65.8% while 34.2% is influenced by other factors